Candidacy for Extracorporeal Life Support in Children After Hematopoietic Cell Transplantation: A Position Paper From the Pediatric Acute Lung Injury and Sepsis Investigators Network's Hematopoietic Cell Transplant and Cancer Immunotherapy Subgroup. Issue 3 (March 2022) - Zinter, Matt S.; McArthur, Jennifer; Duncan, Christine; Adams, Roberta; Kreml, Erin; Dalton, Heidi; Abdel-Azim, Hisham; Rowan, Courtney M.; Gertz, Shira J.; Mahadeo, Kris M.; Randolph, Adrienne G.; Rajapreyar, Prakadeshwari; et al.
Abstract : OBJECTIVES: The last decade has seen improved outcomes for children requiring extracorporeal life support as well as for children undergoing hematopoietic cell transplantation. Thus, given the historically poor survival of hematopoietic cell transplantation patients using extracorporeal life support, the Pediatric Acute Lung Injury and Sepsis Investigators' hematopoietic cell transplantation and cancer immunotherapy subgroup aimed to characterize the utility of extracorporeal life support in facilitating recovery from critical cardiorespiratory illnesses in pediatric hematopoietic cell transplantation patients. DATA SOURCES: All available published data were identified using a set of PubMed search terms for pediatric extracorporeal life support and hematopoietic cell transplantation. STUDY SELECTION: All articles that provided original reports of pediatric hematopoietic cell transplantation patients who underwent extracorporeal life support were included. Sixty-four manuscripts met search criteria. Twenty-four were included as primary reports of pediatric hematopoietic cell transplantation patients who underwent extracorporeal life support (11 were single case reports, four single institution case series, two multi-institution case series, and seven registry reports from Extracorporeal Life Support Organization, Pediatric Heath Information System, and Virtual Pediatric Systems). DATA EXTRACTION: All 24 articles were reviewed by first and last authors and a spread sheet was constructed including sample size, potential biases, and conclusions. DATA SYNTHESIS: Discussions regarding incorporation of available evidence into our clinical practice were held at biannual meetings, as well as through email and virtual meetings. An expert consensus was determined through these discussions and confirmed through a modified Delphi process. CONCLUSIONS: Extracorporeal life support in hematopoietic cell transplantation patients is being used with increasing frequency and potentially improving survival. The Pediatric Acute Lung Injury and Sepsis Investigators hematopoietic cell transplantation-cancer immunotherapy subgroup has developed a framework to guide physicians in decision-making surrounding extracorporeal life support candidacy in pediatric hematopoietic cell transplantation patients. In addition to standard extracorporeal life support considerations, candidacy in the hematopoietic cell transplantation population should consider the following six factors in order of consensus agreement: 1) patient comorbidities; 2) underlying disease necessitating hematopoietic cell transplantation; 3) hematopoietic cell transplantation toxicities, 4) family and patient desires for goals of care; 5) hematopoietic cell transplantation preparatory regimen; and 6) graft characteristics. Although risk assessment may be individualized, data are currently insufficient to clearly delineate ideal candidacy. Therefore, we urge the onco-critical care community to collaborate and capture data to provide better evidence to guide physicians' decision-making in the future.